Development of SAC3-Assisted Digital Learning Media to Enhance Students’ Mathematical Literacy in Matrix Topics - Majid, Ahmad Farham; Amran, Nurul Khofifah; Rahmaniyah, Aulia’ur; Haz, A. Safwan Ibrahim (Mathematics Education Journal, 2025)
The advancement of information and communication technology has driven innovation in education, particularly in the development of learning media aligned with the competencies required in the 21st century. This study aims to develop digital learning media assisted by Smart Apps Creator 3 (SAC3) to enhance students’ mathematical literacy in matrix topics. The development model employed is ADDIE, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. Validation results from subject matter and media experts indicate that the product is highly valid and appropriate for use in the learning process. Practicality and effectiveness testing involving 33 eleventh-grade students (class XI.2) demonstrated that the use of this media significantly improved students’ learning interest, conceptual understanding, and mathematical literacy skills compared to conventional teaching methods. Therefore, SAC3-assisted digital learning media on matrix material offers an innovative solution for enhancing the quality of mathematics instruction in the digital era.